Estudio de factibilidad para creación de una comercializadora de champiñones ostra en la ciudad de Santiago de Cali (2014)
There is currently very little supply to high demand for the marketing of oyster mushrooms, mushroom production and marketing is monopolized by a single variety. The variety of strains of edible mushrooms is very large but have only been marketed heavily calls paris mushrooms or fungi parasol shaped and featuring a visually appealing, hence the idea of commercializing new varieties of edible greater area arises and with better organoleptic its way as a viable alternative to competition on the local, national market. This project started in the formulation of the research problem to perform as well as the reasons for its development; then there is a first contact with the species of fungus to grow describing general aspects of the biology of Pleurotus ostreatus; once you have this knowledge, establishing the place where the culture according to the required environmental parameters can be done for it. The next step is the identification of the materials and equipment needed to carry out the cultivation process and the design scheme of planting and harvesting of Pleurotus ostreatus. After researching about the existing marketing channels for edible fungi within the country and once it is determined the market size for this project, you define how marketing Pleurotus ostreatus be performed, taking into account the requirements and characteristics selected customers that demand the product.